The Effect Of Entrepreneurial Competencies On Business Performance (Empirical Study On Msmes Of Palembang Woven Fabric) - Bainil Yulina; Pridson Mandiangan; Nurul Azizah (International Journal of Science, Technology & Management, 2021)
The aims of this study were to investigate the entrepreneurial competence in Micro, Small and Medium Enterprises (MSMEs) of Palembang woven fabrics, the busniess performance of Micro, Small and Medium Enterprises (MSMEs) of Palembang woven fabrics, and whether entrepreneurial competence affected business performance at Micro, Small and Medium Enterprises (MSMEs) of Palembang woven fabrics. This research employed quantitative method. The population in this study was 90 owners of MSMEs as well as woven fabric craftsmen in the Tuan Kentang Palembang area. The sample used a random sample of 50 respondents. To collect the data, a closed-ended questionnaire was used. For data analysis, Ordinary Least Square was used. The research results showed 3 findings: overall, the entrepreneurial competence in the Palembang woven fabric business was in the high category, the overall performance of the Palembang woven fabric business was in the very high category, and entrepreneurial competence had a positive and significant effect on the business performance of the Palembang woven fabric business.